The RNA–RNA interactome between a phage and its satellite virus reveals a small RNA that differentially regulates gene expression across both genomes. Issue 4 (27th February 2023) - Dunham, Drew T.; Angermeyer, Angus; Seed, Kimberley D.
Abstract: Satellite viruses are present across all domains of life, defined as subviral parasites that require infection by another virus for satellite progeny production. Phage satellites exhibit various regulatory mechanisms to manipulate phage gene expression to the benefit of the satellite, redirecting resources from the phage to the satellite, and often inhibiting phage progeny production. While small RNAs (sRNAs) are well documented as regulators of prokaryotic gene expression, they have not been shown to play a regulatory role in satellite‐phage conflicts. Vibrio cholerae encodes the phage inducible chromosomal island‐like element (PLE), a phage satellite, to defend itself against the lytic phage ICP1. Here, we use Hi‐GRIL‐seq to identify a complex RNA–RNA interactome between PLE and ICP1. Both inter‐ and intragenome RNA interactions were detected, headlined by the PLE sRNA, SviR. SviR is involved in regulating both PLE and ICP1 gene expression uniquely, decreasing ICP1 target translation and affecting PLE transcripts. The striking conservation of SviR across all known PLEs suggests the sRNA is deeply rooted in the PLE‐ICP1 conflict and implicates sRNAs as unidentified regulators of gene expression in phage–satellite interactions. Abstract : The application of Hi‐GRIL‐seq to Vibrio cholerae cells harboring the phage satellite, PLE, during bacteriophage ICP1 infection reveals a vast RNA–RNA interactome between phage and phage satellite. Further investigation into the outcome of these interactions suggests that the PLE‐encoded regulatory RNA SviR base pairs with both PLE and ICP1 target transcripts, resulting in unique regulatory outcomes for satellite‐encoded and phage‐encoded target transcripts.